Silicon modified Kevlar aerogel and preparation method thereof
Silicon modified Kevla aerogel was prepared by combining silicon compounds with Kevla nanofibers by sol-gel method, which solved the problem of insufficient flame retardant performance of existing Kevla aerogels, and achieved excellent flame retardant and thermal insulation performance in high-temperature environments. It is suitable for aviation, construction and high-temperature thermal insulation fields.
Patent Information
- Application Number
- CN202510005036.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-02
- Publication Date
- 2025-03-28
AI Technical Summary
The existing Kevla aerogel has poor flame retardant performance, making it difficult to effectively curb flame spread and suppress smoke generation in high-temperature environments, limiting its application potential in aviation, construction and high-temperature insulation.
Silicon modified Kevla aerogel was prepared by combining Kevla nanofibers with silicon compounds by sol-gel method. The method includes adding Kevlan nanofibers to an alkali solution to prepare a dispersion, adding a silicon compound to modify, followed by gelation and solvent replacement, and finally obtaining a silicon modified Kevlan aerogel with a three-dimensional interconnected nanoporous network structure.
Silicon modified Kevla aerogel exhibits excellent flame retardant and thermal insulation properties under high temperature environments, with a density of 0.112 g cm-3~0.356 g cm-3, a thermal conductivity of 0.0191 W m-1K-1~0.0377 W m-1K-1, and an ultimate oxygen index (LOI) of 31.2~45.7. It can effectively isolate high-temperature heat and oxygen, significantly improving its flame retardant performance.
Smart Images

Figure CN119707437A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of high-efficiency heat-insulating and flame-retardant materials, and specifically relates to a silicon-modified Kevlar aerogel and a preparation method thereof. Background Art
[0002] Energy resources are the key material basis for promoting the rapid and high-quality development of social economy. However, the scarcity of energy resources has become an important factor restricting the overall economic progress. Therefore, the development and utilization of new energy and renewable energy, the improvement of the conversion efficiency of existing energy, and the reduction of energy consumption as much as possible have been considered to be effective strategies to alleviate energy problems. Controlling the release of heat energy by using efficient flame-retardant and thermal insulation materials has become an important energy-saving measure. This method can not only significantly reduce heat loss or heat gain, thereby reducing production costs, but also effectively protect the environment and natural resources. Ideal flame-retardant and thermal insulation materials should effectively curb the spread of flames in high temperature environments, and should also have characteristics such as light weight. Therefore, high-performance materials with lightweight characteristics and efficient flame retardant and thermal insulation functions are gradually becoming the focus of current research.
[0003] Kevlar aerogel has become a high-performance thermal insulation material that has attracted much attention due to its low density, excellent mechanical strength, good thermal stability and chemical stability, showing broad application prospects in the fields of military, aerospace, transportation, construction and textiles. Most of the Kevlar aerogels currently prepared are thin films, which have great limitations in practical applications. There are related studies, such as Chinese patent application number CN201811548700.9 Kevlar aerogel film, its preparation method and application; however, no research on the flame retardant properties of Kevlar aerogel has been reported.
[0004] The flame retardant performance of Kevlar aerogel mainly depends on its own heat resistance. Due to the lack of efficient chemical flame retardant mechanism, its effect in preventing the spread of flames and inhibiting smoke generation is still insufficient. Therefore, it is difficult to provide sufficient flame retardant protection when it is subjected to continuous combustion or open flame attack; and the material has limited heat insulation ability in high temperature environment, which significantly limits its direct application potential in aviation, construction and high temperature insulation.
[0005] Therefore, on the basis of ensuring that the material has low thermal conductivity and high-efficiency thermal insulation performance, further improving its flame retardant properties and successfully synthesizing Kevlar aerogel with excellent flame retardant and thermal insulation effects have always been technical challenges that researchers in this field need to focus on and overcome. Summary of the invention
[0006] In view of the problem that the flame retardant performance of Kevlar aerogel in the prior art is poor, the present invention provides a silicon-modified Kevlar aerogel and a preparation method thereof, which is a novel silicon-modified Kevlar aerogel and a preparation method thereof.
[0007] The technical solution of the present invention is as follows: The silicon-modified Kevlar aerogel of the present invention uses Kevlar nanofibers as initial raw materials, adopts a sol-gel method, adds Kevlar nanofibers into an alkaline solution to prepare a Kevlar dispersion, adds a silicon compound into the solution for modification to obtain a silicon-containing Kevlar dispersion, prepares the silicon-containing Kevlar dispersion into a silicon-containing Kevlar wet gel under set conditions, and finally obtains the silicon-modified Kevlar aerogel through solvent replacement and drying operations at room temperature and pressure.
[0008] The purpose of the present invention is achieved through the following technical solutions: A method for preparing a silicon-modified Kevlar aerogel comprises the following steps: 1) dissolving the silicon compound in an alcohol solvent at a mass ratio of 1:(5-8) and stirring at a constant speed for 30 minutes at a temperature of 10°C to 35°C to allow the silicon compound to be fully alcoholyzed in the alcohol solvent to obtain a silicon compound solution; The silicon compound is one of methyl orthosilicate, ethyl orthosilicate and fumed silica; The alcohol solvent is one of methanol, ethanol, isopropanol and n-butanol; 2) Add Kevlar nanofibers to the alkaline solution at a ratio of (0.5-0.7) g:100 g, and stir at a constant speed for 30 min at a temperature of 10°C to 35°C to obtain a Kevlar dispersion; The alkaline substance in the alkaline solution is potassium hydroxide or sodium hydroxide; The solvent in the alkaline solution is: a mixed solution of a strong polar solvent and an alcohol solvent, wherein the mass ratio of the strong polar solvent to the alcohol solvent is 50%, the strong polar solvent is dimethyl sulfoxide or N,N-dimethylformamide, and the alcohol solvent is methanol or ethanol; The mass ratio of the alkaline substance to the solvent is 1% to 10%; 3) adding the silicon compound solution obtained in step 1) to the Kevlar dispersion obtained in step 2), wherein the mass ratio of the silicon compound solution to the Kevlar dispersion is 1:(1-3), to obtain a silicon-containing Kevlar dispersion; 4) sealing the silicon-containing Kevlar dispersion obtained in step 3) and placing it in a water bath, heating it to a gelling temperature of 70° C. to 80° C. to gel the silicon-containing Kevlar dispersion to obtain a silicon-containing Kevlar wet gel; 5) subjecting the silicon-containing Kevlar wet gel obtained in step 4) to solvent replacement at room temperature to obtain a silicon-containing Kevlar final gel; In the solvent replacement, the replacement solvent used is ethanol, isopropanol or tert-butanol, the number of solvent replacements is 2 to 4 times, and the time for each replacement is 6 hours to 10 hours; 6) Drying the silicon-containing Kevlar final gel prepared in step 5) at room temperature and normal pressure until the mass of the gel no longer changes, thereby obtaining a silicon-modified Kevlar aerogel, wherein the silicon-modified Kevlar aerogel exhibits a three-dimensional interconnected nanoporous network structure and has a density of 0.112 g cm -3 ~0.356 g cm -3 , thermal conductivity is 0.0191W m -1 K -1 ~0.0377W m -1 K -1 , the limiting oxygen index (LOI) is 31.2~45.7.
[0009] Furthermore, the silicon compound in step 1) is preferably methyl orthosilicate; the mass ratio of the silicon compound to the alcohol solvent is preferably 1:6; and the alcohol solvent is preferably ethanol.
[0010] Furthermore, the Kevlar nanofibers described in step 2) are added to the alkaline solution at a ratio of 0.6g:100g; the alkaline substance in the alkaline solution is preferably potassium hydroxide; the solvent in the alkaline solution is preferably a mixed solution of dimethyl sulfoxide and methanol; the mass ratio of the alkaline substance to the solvent is preferably 5%.
[0011] Furthermore, the mass ratio of the silicon compound solution to the Kevlar dispersion in step 3) is preferably 1:2.
[0012] Furthermore, the gelling temperature in step 4) is preferably 70°C.
[0013] Furthermore, in the solvent replacement described in step 5), the replacement solvent used is preferably ethanol, the number of solvent replacements is preferably 3 times, and the time for each replacement is preferably 8 hours; Furthermore, the normal pressure in step 6) is a standard atmospheric pressure.
[0014] The present invention also relates to a silicon-modified Kevlar aerogel obtained by the above-mentioned method for preparing a silicon-modified Kevlar aerogel, wherein the silicon-modified Kevlar aerogel exhibits a three-dimensional interconnected nanoporous network structure and has a density of 0.112 g cm -3 ~0.356 g cm -3 , thermal conductivity is 0.0191 W m -1 K -1 ~0.0377 W m -1 K -1The limiting oxygen index (LOI) is 31.2-45.7, and it has the characteristics of low density, low thermal conductivity and high efficiency flame retardancy.
[0015] Compared with the prior art, the present invention has the following advantages: 1. The preparation method of a silicon-modified Kevlar aerogel described in the present invention introduces silicon into the Kevlar aerogel (the fourth step), which not only ensures the low thermal conductivity characteristics of the Kevlar aerogel, but also enables the Kevlar aerogel to form a silicon dioxide layer during the combustion process. The silicon dioxide layer can not only effectively isolate the material from contact with external oxygen, but also effectively prevent external high-temperature heat from being transferred to the inside of the material, preventing the material from further decomposition or combustion, thereby improving the flame retardant properties of the Kevlar aerogel.
[0016] 2. The silicon-modified Kevlar aerogel prepared by the present invention has the characteristics of low thermal conductivity, high-efficiency flame retardancy and heat insulation; the density of the silicon-modified Kevlar aerogel prepared by the method of the present invention is 0.112 g cm -3 ~0.356 g cm -3 , thermal conductivity is 0.0191 W m -1 K -1 ~0.0377 W m -1 K -1 , LOI is 31.2-45.7 (when the LOI value is greater than 27, the material can be regarded as a flame retardant material, and the higher the LOI value, the better the flame retardant performance of the material), indicating that the silicon-modified Kevlar aerogel of the present invention has excellent flame retardant and heat-insulating properties and can meet the use requirements of aerospace, transportation, construction, clothing and other aspects. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 It is an overall flow chart of a method for preparing a silicon-modified Kevlar aerogel according to the present invention. DETAILED DESCRIPTION
[0018] The present invention is further described in detail below by way of examples, but these examples should not be considered as limiting the present invention.
[0019] Embodiment 1: A method for preparing silicon-modified Kevlar aerogel, such as Figure 1 As shown, the following steps are included: The technical solution of the present invention is further described below with reference to examples: like Figure 1 As shown, embodiment 1 of the present invention includes the following steps: Step 1: First, dissolve 4 g of a silicon compound in 20 g of ethanol, wherein the silicon compound is methyl orthosilicate, and the mass ratio of the silicon compound to the ethanol is 1:5, and stir at a constant speed for 30 min at room temperature to allow the silicon compound to be fully alcoholyzed in the ethanol to obtain a silicon compound solution; Step 2: adding 0.5 g of Kevlar nanofibers to 100 g of a 5% alkaline solution, stirring at a constant speed for 30 min at room temperature to obtain a Kevlar dispersion; the alkaline substance in the alkaline solution is potassium hydroxide; Step 3: adding the silicon compound solution obtained in the first step to the Kevlar dispersion obtained in the second step to obtain a silicon-containing Kevlar dispersion, wherein the mass ratio of the silicon compound solution to the Kevlar dispersion is 1:1; Step 4: The silicon-containing Kevlar dispersion obtained in the third step is sealed and placed in a water bath, and the temperature is raised to 70° C. to gel the silicon-containing Kevlar dispersion to obtain a silicon-containing Kevlar wet gel; Step 5: Solvent-displace the silicon-containing Kevlar wet gel obtained in the fourth step with ethanol at room temperature for a total of 3 times to obtain a silicon-containing Kevlar final gel; Step 6: Dry the silicon-containing Kevlar final gel prepared in the fifth step at room temperature and normal pressure to obtain silicon-modified Kevlar aerogel.
[0020] The density of the final prepared silicon-modified Kevlar aerogel is 0.297 g cm -3 , thermal conductivity is 0.0328 W m -1 K -1 , the LOI value is 44.5.
[0021] Embodiment 2: A method for preparing silicon-modified Kevlar aerogel, such as Figure 1 As shown, the following steps are included: Step 1: First, dissolve 2.86 g of a silicon compound in 20 g of methanol, wherein the silicon compound is methyl orthosilicate, and the mass ratio of the silicon compound to methanol is 1:7, and stir at a constant speed for 30 minutes at room temperature to allow the silicon compound to be fully alcoholyzed in methanol to obtain a silicon compound solution; Step 2: adding 0.6 g of Kevlar nanofibers to 100 g of a 5% alkaline solution, stirring at a constant speed for 30 min at room temperature to obtain a Kevlar dispersion; the alkaline substance in the alkaline solution is potassium hydroxide; Step 3: adding the silicon compound solution obtained in the first step to the Kevlar dispersion obtained in the second step to obtain a silicon-containing Kevlar dispersion, wherein the mass ratio of the silicon compound solution to the Kevlar dispersion is 1:2; Step 4: The silicon-containing Kevlar dispersion obtained in the third step is sealed and placed in a water bath, and the temperature is raised to 70° C. to gel the silicon-containing Kevlar dispersion to obtain a silicon-containing Kevlar wet gel; Step 5: Solvent-displace the silicon-containing Kevlar wet gel obtained in the fourth step with ethanol at room temperature for a total of 3 times to obtain a silicon-containing Kevlar final gel; Step 6: Dry the silicon-containing Kevlar final gel prepared in the fifth step at room temperature and normal pressure to obtain silicon-modified Kevlar aerogel.
[0022] The density of the final prepared silicon-modified Kevlar aerogel is 0.198 g cm -3 , thermal conductivity is 0.026 W m -1 K -1 , the LOI value is 36.6.
[0023] Embodiment 3: A method for preparing silicon-modified Kevlar aerogel, such as Figure 1 As shown, the following steps are included: Step 1: First, dissolve 4 g of a silicon compound in 20 g of ethanol, wherein the silicon compound is ethyl orthosilicate, and the mass ratio of the silicon compound to the ethanol is 1:5, and stir at a constant speed for 30 min at room temperature to allow the silicon compound to be fully alcoholyzed in the ethanol to obtain a silicon compound solution; Step 2: adding 0.6 g of Kevlar nanofibers to 100 g of 1% alkaline solution by mass, stirring at a constant speed for 30 min at room temperature to obtain a Kevlar dispersion; the alkaline substance in the alkaline solution is sodium hydroxide; Step 3: adding the silicon compound solution obtained in the first step to the Kevlar dispersion obtained in the second step to obtain a silicon-containing Kevlar dispersion, wherein the mass ratio of the silicon compound solution to the Kevlar dispersion is 1:2; Step 4: The silicon-containing Kevlar dispersion obtained in the third step is sealed and placed in a water bath, and the temperature is raised to 75° C. to gel the silicon-containing Kevlar dispersion to obtain a silicon-containing Kevlar wet gel; Step 5: Solvent-displace the silicon-containing Kevlar wet gel obtained in the fourth step with ethanol at room temperature for a total of 3 times to obtain a silicon-containing Kevlar final gel; Step 6: Dry the silicon-containing Kevlar final gel prepared in the fifth step at room temperature and normal pressure to obtain silicon-modified Kevlar aerogel.
[0024] The density of the final prepared silicon-modified Kevlar aerogel is 0.321 g cm -3 , thermal conductivity is 0.0349 W m -1 K -1 , the LOI value is 43.2.
[0025] Embodiment 4: A method for preparing silicon-modified Kevlar aerogel, such as Figure 1 As shown, the following steps are included: Step 1: First, dissolve 2.5 g of a silicon compound in 20 g of isopropanol, wherein the silicon compound is ethyl orthosilicate, and the mass ratio of the silicon compound to isopropanol is 1:8, and stir at a constant speed for 30 min at room temperature to allow the silicon compound to be fully alcoholyzed in the isopropanol to obtain a silicon compound solution; Step 2: adding 0.7 g of Kevlar nanofibers to 100 g of an alkaline solution having a mass ratio of 10%, stirring at a constant speed for 30 min at room temperature to obtain a Kevlar dispersion; the alkaline substance in the alkaline solution is sodium hydroxide; Step 3: adding the silicon compound solution obtained in the first step to the Kevlar dispersion obtained in the second step to obtain a silicon-containing Kevlar dispersion, wherein the mass ratio of the silicon compound solution to the Kevlar dispersion is 1:3; Step 4: The silicon-containing Kevlar dispersion obtained in the third step is sealed and placed in a water bath, and the temperature is raised to 75° C. to gel the silicon-containing Kevlar dispersion to obtain a silicon-containing Kevlar wet gel; Step 5: Solvent-displace the silicon-containing Kevlar wet gel obtained in the fourth step with ethanol at room temperature for a total of 3 times to obtain a silicon-containing Kevlar final gel; Step 6: Dry the silicon-containing Kevlar final gel prepared in the fifth step at room temperature and normal pressure to obtain silicon-modified Kevlar aerogel.
[0026] The density of the final prepared silica-modified Kevlar aerogel is 0.17 g cm -3 , thermal conductivity is 0.0234 W m -1 K -1 , the LOI value is 31.3.
[0027] Embodiment 5: A method for preparing silicon-modified Kevlar aerogel, such as Figure 1 As shown, the following steps are included: Step 1: First, dissolve 4 g of a silicon compound in 20 g of ethanol, wherein the silicon compound is fumed silica, and the mass ratio of the silicon compound to the ethanol is 1:5, and stir at a constant speed for 30 min at room temperature to allow the silicon compound to be fully alcoholyzed in the ethanol to obtain a silicon compound solution; Step 2: adding 0.7 g of Kevlar nanofibers to 100 g of a 5% alkaline solution, stirring at a constant speed for 30 min at room temperature to obtain a Kevlar dispersion; the alkaline substance in the alkaline solution is sodium hydroxide; Step 3: adding the silicon compound solution obtained in the first step to the Kevlar dispersion obtained in the second step to obtain a silicon-containing Kevlar dispersion, wherein the mass ratio of the silicon compound solution to the Kevlar dispersion is 1:2; Step 4: The silicon-containing Kevlar dispersion obtained in the third step is sealed and placed in a water bath, and the temperature is raised to 70° C. to gel the silicon-containing Kevlar dispersion to obtain a silicon-containing Kevlar wet gel; Step 5: Solvent-displace the silicon-containing Kevlar wet gel obtained in the fourth step with ethanol at room temperature for a total of 3 times to obtain a silicon-containing Kevlar final gel; Step 6: Dry the silicon-containing Kevlar final gel prepared in the fifth step at room temperature and normal pressure to obtain silicon-modified Kevlar aerogel.
[0028] The density of the final prepared silica-modified Kevlar aerogel is 0.324 g cm -3 , thermal conductivity is 0.0352 W m -1 K -1 , the LOI value is 43.5.
[0029] Embodiment 6: A method for preparing silicon-modified Kevlar aerogel, such as Figure 1 As shown, the following steps are included: Step 1: First, dissolve 2.5 g of a silicon compound in 20 g of ethanol, wherein the silicon compound is fumed silica, and the mass ratio of the silicon compound to the ethanol is 1:8, and stir at a constant speed for 30 min at room temperature to allow the silicon compound to be fully alcoholyzed in the ethanol to obtain a silicon compound solution; Step 2: adding 0.7 g of Kevlar nanofibers to 100 g of a 5% alkaline solution, stirring at a constant speed for 30 min at room temperature to obtain a Kevlar dispersion; the alkaline substance in the alkaline solution is potassium hydroxide; Step 3: adding the silicon compound solution obtained in the first step to the Kevlar dispersion obtained in the second step to obtain a silicon-containing Kevlar dispersion, wherein the mass ratio of the silicon compound solution to the Kevlar dispersion is 1:3; Step 4: The silicon-containing Kevlar dispersion obtained in the third step is sealed and placed in a water bath, and the temperature is raised to 70° C. to gel the silicon-containing Kevlar dispersion to obtain a silicon-containing Kevlar wet gel; Step 5: Solvent-displace the silicon-containing Kevlar wet gel obtained in the fourth step with ethanol at room temperature for a total of 3 times to obtain a silicon-containing Kevlar final gel; Step 6: Dry the silicon-containing Kevlar final gel prepared in the fifth step at room temperature and normal pressure to obtain silicon-modified Kevlar aerogel.
[0030] The density of the final prepared silicon-modified Kevlar aerogel is 0.174 g cm -3 , thermal conductivity is 0.0233 W m -1 K -1 , the LOI value is 31.6.
[0031] Embodiment 7: A method for preparing silicon-modified Kevlar aerogel, such as Figure 1 As shown, the following steps are included: Step 1: First, dissolve 3.33 g of a silicon compound in 20 g of ethanol, wherein the silicon compound is methyl orthosilicate, and the mass ratio of the silicon compound to the ethanol is 1:6, and stir at a constant speed for 30 min at room temperature to allow the silicon compound to be fully alcoholyzed in the ethanol to obtain a silicon compound solution; Step 2: adding 0.6 g of Kevlar nanofibers to 100 g of a 5% alkaline solution, stirring at a constant speed for 30 min at room temperature to obtain a Kevlar dispersion; the alkaline substance in the alkaline solution is potassium hydroxide; Step 3: adding the silicon compound solution obtained in the first step to the Kevlar dispersion obtained in the second step to obtain a silicon-containing Kevlar dispersion, wherein the mass ratio of the silicon compound solution to the Kevlar dispersion is 1:1; Step 4: The silicon-containing Kevlar dispersion obtained in the third step is sealed and placed in a water bath, and the temperature is raised to 70° C. to gel the silicon-containing Kevlar dispersion to obtain a silicon-containing Kevlar wet gel; Step 5: Solvent-displace the silicon-containing Kevlar wet gel obtained in the fourth step with ethanol at room temperature for a total of 3 times to obtain a silicon-containing Kevlar final gel; Step 6: Dry the silicon-containing Kevlar final gel prepared in the fifth step at room temperature and normal pressure to obtain silicon-modified Kevlar aerogel.
[0032] The density of the final prepared silicon-modified Kevlar aerogel is 0.241 g cm -3 , thermal conductivity is 0.0292 W m -1 K -1 , the LOI value is 42.2.
[0033] In the above-mentioned process of preparing silicon-modified Kevlar aerogel: In the first step, the silicon compound is added to the alcohol solvent in order to fully alcoholize the silicon compound to obtain a silicon compound solution (the role of the alcohol solvent is to promote the alcoholysis of the silicon compound, and the type of the alcohol solvent has little effect on the flame retardant and heat insulation properties of the Kevlar aerogel); The second step is to add Kevlar nanofibers into the alkaline solution in order to obtain a Kevlar dispersion; The third step is to add the silicon compound solution into the Kevlar dispersion to fully mix and modify the Kevlar dispersion; The fourth step is to seal the silicon-containing Kevlar dispersion and then heat it to promote its gelation at high temperature to obtain the silicon-containing Kevlar wet gel; The fifth step of solvent replacement is to replace the organic solvent in the silicon-containing Kevlar wet gel with ethanol to obtain the silicon-containing Kevlar final gel; The sixth step of normal pressure drying is to remove excess solvent in the silicon-containing Kevlar final gel to obtain silicon-modified Kevlar aerogel.
[0034] During the preparation process, as long as factors such as the type of alcohol solvent, drying temperature, gelation temperature, etc. are within the above range, the effects on the density, thermal conductivity, and flame retardancy of the silicon-modified Kevlar aerogel can be basically ignored.
[0035] The density, thermal conductivity and flame retardant properties of silicon-modified Kevlar aerogel are mainly affected by the type of silicon compound, the mass ratio of silicon compound to alcohol solvent, the mass ratio of silicon compound solution to Kevlar dispersion, and the mass of Kevlar nanofiber. The type of silicon compound has a significant effect on the flame retardant properties of the material, among which the Kevlar aerogel modified with fumed silica has a higher oxygen index; the mass ratio of silicon compound to alcohol solvent has a significant effect on the density, thermal conductivity and flame retardant properties of the material. The larger the mass ratio, the greater the density of the material, the greater the thermal conductivity, and the better the flame retardant properties; at the same time, the larger the mass ratio of silicon compound solution to Kevlar dispersion, the smaller the density of the aerogel, the lower the thermal conductivity, and the better the flame retardant properties; the mass of Kevlar nanofiber has a significant effect on the density and thermal conductivity of the material. The smaller the mass, the lower the density and thermal conductivity.
[0036] The specific preparation process parameters and performance parameters of silicon-modified Kevlar aerogel are shown in Table 1.
[0037] Table 1 Preparation process parameters and performance parameters of silicon-modified Kevlar aerogel
[0038] Comparative Example 1: The difference between Comparative Example 1 and Example 1 is that the preparation of the silicon compound solution in step 1) is omitted, and the other steps are the same as those in Example 1; The density of the obtained Kevlar aerogel is 0.212 g cm -3 , thermal conductivity is 0.0286 W m -1 K -1 , the LOI value is 28.3.
[0039] The results show that the introduction of silicon can improve the flame retardant and thermal insulation properties of Kevlar aerogel, making it more stable and reliable in high temperature environments.
[0040] Comparative Example 2: The difference between Comparative Example 2 and Example 1 is that in step 3), the mass ratio of the silicon compound solution to the Kevlar dispersion is changed to 5:1, and the rest is the same as in Example 1; Kevlar aerogel is not available.
[0041] The results show that the introduction of excessive silicon will make the gel formation process difficult to control, thereby destroying the reaction conditions of Kevlar aerogel and failing to obtain Kevlar aerogel.
[0042] Comparative Example 3: The difference between Comparative Example 3 and Example 1 is that in step 2), the mass of the Kevlar fiber is changed to 5 g, and the rest is the same as in Example 1; The density of the obtained Kevlar aerogel is 0.447 g cm -3 , thermal conductivity is 0.0483 W m -1 K -1 , the LOI value is 27.2.
[0043] The results show that the more Kevlar fibers are added, the greater the density of the material, which leads to an increase in the thermal conductivity of the material, poorer thermal insulation performance, and no improvement in the flame retardant properties of the material. The amount of Kevlar fibers added needs to be controlled.
[0044] The above are only preferred implementations of the present invention. The protection scope of the present invention is not limited to the above embodiments. Various process schemes that are not substantially different from the concept of the present invention are within the protection scope of the present invention.
Claims
1. A method for preparing silicon-modified Kevlar aerogel, characterized in that: The following steps are involved: 1) dissolving the silicon compound in an alcohol solvent at a mass ratio of 1:(5-8) and stirring at a constant speed for 30 minutes at a temperature of 10°C to 35°C to allow the silicon compound to be fully alcoholyzed in the alcohol solvent to obtain a silicon compound solution; The silicon compound is one of methyl orthosilicate, ethyl orthosilicate and fumed silica; The alcohol solvent is one of methanol, ethanol, isopropanol and n-butanol; 2) Add Kevlar nanofibers to the alkaline solution at a ratio of (0.5-0.7) g:100 g, and stir at a constant speed for 30 min at a temperature of 10°C to 35°C to obtain a Kevlar dispersion; The alkaline substance in the alkaline solution is potassium hydroxide or sodium hydroxide; The solvent in the alkaline solution is: a mixed solution of a strong polar solvent and an alcohol solvent, wherein the mass ratio of the strong polar solvent to the alcohol solvent is 50%, the strong polar solvent is dimethyl sulfoxide or N,N-dimethylformamide, and the alcohol solvent is methanol or ethanol; The mass ratio of the alkaline substance to the solvent is 1% to 10%; 3) adding the silicon compound solution obtained in step 1) to the Kevlar dispersion obtained in step 2), wherein the mass ratio of the silicon compound solution to the Kevlar dispersion is 1:(1-3), to obtain a silicon-containing Kevlar dispersion; 4) sealing the silicon-containing Kevlar dispersion obtained in step 3) and placing it in a water bath, heating it to a gelling temperature of 70° C. to 80° C. to gel the silicon-containing Kevlar dispersion to obtain a silicon-containing Kevlar wet gel; 5) subjecting the silicon-containing Kevlar wet gel obtained in step 4) to solvent replacement at room temperature to obtain a silicon-containing Kevlar final gel; In the solvent replacement, the replacement solvent used is ethanol, isopropanol or tert-butanol, the number of solvent replacements is 2 to 4 times, and the time for each replacement is 6 hours to 10 hours; 6) Drying the silicon-containing Kevlar final gel prepared in step 5) at room temperature and normal pressure until the mass of the gel no longer changes, thereby obtaining a silicon-modified Kevlar aerogel, wherein the silicon-modified Kevlar aerogel exhibits a three-dimensional interconnected nanoporous network structure and has a density of 0.112 g cm -3 ~0.356 g cm -3 , thermal conductivity is 0.0191 W m -1 K -1 ~0.0377 W m -1 K -1 , the limiting oxygen index is 31.2~45.
7.
2. The method for preparing a silicon-modified Kevlar aerogel according to claim 1, characterized in that: The silicon compound in step 1) is methyl orthosilicate; the mass ratio of the silicon compound to the alcohol solvent is 1:6; and the alcohol solvent is ethanol.
3. The method for preparing a silicon-modified Kevlar aerogel according to claim 1, characterized in that: The Kevlar nanofibers described in step 2) are added to the alkaline solution at a ratio of 0.6g:100g; the alkaline substance is potassium hydroxide; the solvent is a mixed solution of dimethyl sulfoxide and methanol; the mass ratio of the alkaline substance to the solvent is 5%.
4. The method for preparing a silicon-modified Kevlar aerogel according to claim 1, characterized in that: The mass ratio of the silicon compound solution to the Kevlar dispersion in step 3) is 1:
2.
5. The method for preparing a silicon-modified Kevlar aerogel according to claim 1, characterized in that: The gelling temperature described in step 4) is 70°C.
6. The method for preparing a silicon-modified Kevlar aerogel according to claim 1, characterized in that: In the solvent replacement described in step 5), the replacement solvent used is ethanol, the number of solvent replacements is 3 times, and the time for each replacement is 8 hours.
7. A silicon-modified Kevlar aerogel, characterized in that: The silicon-modified Kevlar aerogel prepared by the method for preparing the silicon-modified Kevlar aerogel according to any one of claims 1 to 6 has a three-dimensional interconnected nanoporous network structure and a density of 0.112 g cm -3 ~0.356 g cm -3 , thermal conductivity is 0.0191 W m -1 K -1 ~0.0377 W m -1 K -1 , the limiting oxygen index is 31.2~45.7, and it has low density, low thermal conductivity and high efficiency flame retardant properties.
Citation Information
Patent Citations
Kevlar aerogel film, and preparation method and application thereof
CN109608686A